Antibody-based HIV-1 vaccines: recent developments and future directions - Montefiori, D; Sattentau, Q; Flores, J; Esparza, J; Mascola, J (Public Library of Science, 2007)
A summary report from a Global HIV Vaccine Enterprise Working Group